Core assessment and training - Brumitt, Jason (Human Kinetics, 2010)
Core health prevents injuries, improves athletic performance and helps rehabilitation. Whether you are a personal trainer, strength coach or rehabilitation professional, this book covers various aspects of core training, from basic to advanced core exercises, stretches and plyometrics.